2012
DOI: 10.1007/s12105-012-0406-z
|View full text |Cite
|
Sign up to set email alerts
|

B7-H1 Expression Model for Immune Evasion in Human Papillomavirus-Related Oropharyngeal Squamous Cell Carcinoma

Abstract: Human papillomavirus (HPV) is associated with oropharyngeal squamous cell carcinomas. Persistent viral infection is postulated to lead to carcinogenesis, although infection of benign adjacent epithelium is not typically observed. It is known that immune evasive tumor cells can provide an ideal niche for a virus. The B7-H1/ PD-1 cosignaling pathway plays an important role in viral immune evasion by rendering CD8? cytotoxic T cells anergic. We hypothesized that HPV-related oropharyngeal squamous cell carcinomas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
5
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 40 publications
4
105
5
3
Order By: Relevance
“…Another study evaluating oropharyngeal SCC showed that PD-L1 was expressed in 49.2% and 34.1% of HPV mRNA-positive and -negative cases, respectively. No correlation was evident between PD-L1 status and survival [49]. A more recent study of 340 NSCLC patients, including 178 SCC patients, found that the PD-L1 mRNA and protein expression levels, as assessed via in situ hybridization and tissue microarray, respectively, were in agreement, and that high PD-L1 expression levels were associated with elevated TILs and better survival [50].…”
Section: Pd-l1 Expression In Scc and The Prognostic Implications Thereofmentioning
confidence: 96%
“…Another study evaluating oropharyngeal SCC showed that PD-L1 was expressed in 49.2% and 34.1% of HPV mRNA-positive and -negative cases, respectively. No correlation was evident between PD-L1 status and survival [49]. A more recent study of 340 NSCLC patients, including 178 SCC patients, found that the PD-L1 mRNA and protein expression levels, as assessed via in situ hybridization and tissue microarray, respectively, were in agreement, and that high PD-L1 expression levels were associated with elevated TILs and better survival [50].…”
Section: Pd-l1 Expression In Scc and The Prognostic Implications Thereofmentioning
confidence: 96%
“…But very little literature has been published correlating HPV positivity and oral cancer lesions with immune-checkpoint inhibitors. Two different studies by LyfordPike et al and Upko et al have shown that HPVpositive oral cancer cases overexpressed PD-L1 when compared with HPV negative cases [11,12]. They also established that HPV-positive cases possess PD-1 overexpressing CD8, CD4 and TILs in their tumor microenvironment.…”
Section: Pd-1/pd-l1 In Oral Cancers and Hpv Infectionsmentioning
confidence: 94%
“…Head and neck cancers not associated with HPV infection likely also co-opt immune regulatory mechanisms to facilitate their progression. Increased PD-L1 expression similarly has been detected on tobacco-and alcohol-induced SCCs of the head and neck (11,(13)(14)(15)(16), as well as other virally mediated tumors, including nasopharyngeal carcinoma and natural killer T (NKT)-cell lymphoma (17). HPV-targeted vaccination is recommended for adolescent boys and girls to prevent incident HPV infection.…”
Section: Tumor Developmentmentioning
confidence: 99%
“…One study identified PD-1 þ -infiltrating T cells as a favorable prognostic factor in HPV-associated oropharyngeal cancer (28). In other studies of patients with cancers of the oral cavity and oropharynx, PD-L1 expression was not prognostic (13), or was indicative of distant metastases but not local recurrence or overall survival (16).…”
Section: Immune Reactivity and Prognosismentioning
confidence: 99%